PENINGKATAN HASIL BELAJAR IPAS MELALUI PENDEKATAN TaRL BERBANTUAN MEDIA PUZZLE DI KELAS III SDN 4 MEGUGEDE - Surasih Septianingrum, Miya; Nurhabibah, Prabawati; Setiawan, Endra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low learning outcomes of students in the IPAS subject, particularly in the topics of landforms and human adaptation, have become one of the main issues faced in class 3A at SDN 4 Megugede. Students demonstrated unequal achievement levels, with the majority falling into the basic and intermediate ability groups, and showing low active participation during the learning process. This issue was further exacerbated by the use of lecture-based methods and conventional media, which were less effective in encouraging full student engagement. Based on these conditions, it is necessary to implement both an instructional approach and learning media that are tailored to students’ abilities while also promoting active participation. This study aims to improve student learning outcomes through the implementation of the Teaching at the Right Level (TaRL) approach combined with the Problem-Based Learning (PBL) model supported by puzzle-based media. This classroom action research (CAR) was conducted in two cycles, involving the stages of planning, implementation, observation, and reflection. The research subjects consisted of 35 students grouped into three ability levels: advanced, intermediate, and basic. The results showed a significant improvement in student learning outcomes. Mastery learning increased from 41% in the first cycle to 76% in the second cycle. These findings indicate that the combination of the TaRL approach and the PBL model, supported by puzzle media, can enhance student engagement, motivation, and understanding of the subject matter. Therefore, this strategy is recommended as an innovative alternative in teaching IPAS at the elementary school level.